Public opinion and special interests in American environmental politics - Elise Grieg (ETH Zurich, CER-ETH - Center of Economic Research, 2021)
To shed light on the political inertia around environmental legislation, I study the response of US senators to public opinion while controlling for special interest pressure. I combine data on public opinion (PO) on climate change - estimated by multilevel regression with poststratification - with campaign contributions from the extractive industries to indicate special interest (SI) influence, and use senator fixed effects, instrumental variables and the timing of senate elections for identification. PO has a strong impact on environmental legislation. The effects are different for the two parties: Republicans react to PO in election cycles, whereas Democrats are responsive through their whole term. The responsiveness of elected officials to environmental opinion is surprising: while Americans often favour environmental regulation in general, they tend to consider it as of low importance. I discuss possible explanations.
Keywords: 330